(untitled) (Journal of Hama University, 2022)
This study aimed to determine the elements of applying the dimensions of interactive marketing, which are represented in (Trust; Commitment; Interaction) on the hotels in Hama Governorate. The researcher followed the descriptive approach in his study, and a set of methods, including relying on secondary and primary data, using a questionnaire that was designed through the researcher’s review of the published literature, and it was distributed to (235) respondents, from which (234) were recovered, and (223) were valid questionnaires for analysis. The study population consisted of five hotel clients in Hama Governorate, and then the SPSS program was relied upon as a tool to analyze the available data in order to describe each dimension of the study. The study found results, the most important of which is that interactive marketing contributes to building a strong relationship between the hotel and its customers through the attraction and payment technology that contributes to strengthening the relationship with customers, it also provides the opportunity for hotels to describe their websites in an attractive manner and their ability to contain large amounts of information, And at a low cost, it helps the customer to compare competing hotels.